STUDYING ANIMAL TAXONOMY THROUGH SYSTEM-ACTIVITY PROJECTS (7th GRADE) - Asrorova Odinaoy (International Scientific and Current Research Conferences, 2025)
This article presents a feasible methodology for teaching animal taxonomy in grade 7 through a system-activity approach that integrates project-based inquiry, field observation, and representational work with dichotomous keys and simple phylogenetic trees. The design addresses common difficulties in classification—memorization without mechanism, confusion between morphological traits and ecological roles, and weak transfer to unfamiliar organisms—by organizing learning around purposeful activity with authentic specimens and datasets. Over three weeks, students conduct a local biodiversity mini-survey, construct and iteratively refine trait matrices, design and test identification keys, and justify taxonomic decisions with evidence and reasoning. A quasi-experimental evaluation with pre/post concept inventory, performance rubrics, and written explanations indicates substantial gains in identifying diagnostic characters, distinguishing convergent similarities from taxonomically informative homologies, and applying keys to novel cases. Classroom discourse shifts from naming to explaining, and learners demonstrate improved argumentation grounded in observable traits and simple evolutionary ideas. The study concludes that system-activity projects provide coherence, motivation, and durable understanding while remaining implementable in ordinary school conditions.